The Effect Of Preventive Exercises During Deceleration On The Anterior Cruciate Ligament (ACL) In Preventing Sudden Injuries In Young Football Players - M.s. Nawwar Muthanna Subhi (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Objectives. This study aimed (1) to develop preventive exercises that target sudden movements during deceleration and rotation in youth football, and (2) to examine the effects of these exercises on selected performance and biochemical indicators linked to knee-joint injury risk. Materials and Methods. A single-group pretest-posttest experimental design was used. Participants were six youth football players from Al-Furat Sports Club. The program was implemented from March 22 to May 22, 2025 (24 sessions; 3 sessions/week; 25–35 minutes/session; intensity 55–80%). Pretests were conducted on March 18, 2025, and posttests on May 24, 2025. Outcomes included lower-limb explosive power assessed via the standing broad jump and serum creatine phosphokinase (CPK) activity (U/L). Paired-sample t-tests were used with α = 0.05. Results. Significant improvements were observed after the intervention. Explosive power (standing broad jump distance) increased from 2.20 ± 0.29 m to 3.05 ± 0.92 m (t = 8.057; p < 0.001). CPK changed from 293.50 ± 43.79 U/L to 366.17 ± 47.89 U/L (t = 12.507; p < 0.001). Conclusions. Preventive exercises focusing on controlled deceleration and rotation were associated with meaningful improvements in lower-limb explosive power and significant changes in CPK response. These findings support integrating structured preventive exercise components into youth football training, alongside periodic monitoring of musculoskeletal and biochemical indicators.